ENDOPHYTIC PESTALOTIOPSIS SPECIES FROM ANDAMAN ISLANDS: A POTENTIAL PANCREATIC LIPASE INHIBITOR - Sarkar, Subha Jyoti; Dioundi, Divya; Gupta, Mahiti (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: Obesity is the major cause of deaths worldwide. Inhibition of enzymes involved in breakdown of fats can be a good way for obesity management. Pancreatic lipase (PL) causes 50-70% degradation of ingested fats. The aim of this work is to explore the endophytic fungi from untapped biodiversity of Andaman Islands for PL inhibitors. Methods: In the current report, culture broths of 39 endophytic fungi from different curative plants of coastal regions of India have been tested for their potential PL inhibitory activity. The bioactive compound was thus isolated, purified, and analyzed using gas chromatography. Results: It was found that inhibitory concentration of a compound (Rf=0.64) isolated from crude hexane extract of endophytic fungal isolate from Citrus limon was 15.46 Î¼g/ml. Gas chromatogram of the extract showed the presence of caryophyllene which might be responsible for the particular activity. The bioactive fungus was microscopically identified as Pestalotiopsis species. Conclusion: As caryophyllene is component of many oils and is non-toxic, so it can be potential source of safe and effective anti-obesity drug. Â